Asuhan Keperawatan Jiwa Pada Pasien Dengan Halusinasi Pendengaran Dan Penglihatan Di Wisma Flamboyan Rsj. Prof. Dr. Hb. Saanin Padang - Puteri Afifah Maharanie; Ramaita .; Dwi Happy Anggia Sari; Vivi Yuderna (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Hallucinations are false perceptual distortions that occur in maladaptive neurobiological responses, patients actually experience sensory distortions, but respond to them as real. WHO data in 2024 shows that mental disorders have increased to exceed 1.1 billion people. Based on preliminary data obtained from Prof. HB Saanin Mental Hospital, Padang in 2026, the most common nursing problem in the last three years was hallucinations with a total of 17,446 patients. This study aims to apply psychiatric nursing care to patients with hallucinations at Prof. HB Saanin Mental Hospital, Padang. The method used in this scientific paper is a case study with a nursing process approach that includes assessment, diagnosis, planning, implementation, and evaluation. The implementation of nursing care to patients was carried out from February 14 to 18, 2026, with 5 visits. The results of the assessment showed that the patient experienced signs and symptoms of hallucinations in the form of hearing whispers and seeing shadows. The main nursing diagnosis was hallucinations with a companion diagnosis of Self-Care Deficit (DPD). The results of the implementation of Mental Health Nursing Care showed that the patient was able to control his hallucinations independently through implementation strategies (SP) 1-4. After the hallucination management nursing intervention was carried out, these results showed that the implementation of implementation strategies was effective in helping patients control hallucinations and improving self-care skills. Through this study, it is hoped that everyone can understand the importance of mental health nursing care, thereby increasing awareness in maintaining and preserving mental health, and implementing behaviors that support the achievement of mental well-being in everyday life.